Real-time elastography “FibroScan” compared to simple non-invasive screening tools in the assessment of liver fibrosis in non-alcoholic fatty liver patients - Ayman Mohamed Shamseya; Mohamed Tamer Afify; Hussam Ahmed Shawki Fayad; Mohamed Mahmoud Elshafey (Egyptian Liver Journal, 2022)
Abstract Background and aim Non-alcoholic fatty liver disease (NAFLD) and its subtype non-alcoholic steatohepatitis (NASH) are increasing worldwide. NASH is characterized by active liver inflammation with severe consequences including progressive fibrosis, cirrhosis, and eventually hepatocellular carcinoma. In Egypt, the prevalence of NAFLD diagnosed by ultrasound is about 65.3% in children and 62.7% in adults. Liver biopsy, the only reliable method of differentiating simple steatosis from NASH, has a major disadvantage of being an invasive procedure with various complications. Serum tests have limitations including non-specificity for liver inflammation and affection by clearance rates. This study aimed to assess the reliability of simple non-invasive tests for liver fibrosis (namely fibrosis-4 “FIB-4” score and NAFLD fibrosis score) in comparison with real-time elastography (RTE or FibroScan) in patients diagnosed with NAFLD. Patients and methods This observational prospective case–control study was conducted on 100 cases with NAFLD and 30 healthy subjects. All patients and controls were subjected to serological (FIB-4 score and NAFLD fibrosis score) and radiological (ultrasonography and RTE) assessments of liver fibrosis. Results In advanced FIB-4 score ≥ F3, there was a good correlation between the findings of the RTE and each of the FIB-4 scores (with a sensitivity of 90%, specificity of 93.3%, positive predictive value (PPV) of 60%, negative predictive value (NPV) of 98.8%, with a total accuracy of 93%), NAFLD fibrosis score (with a sensitivity of 52.6%, specificity of 93.8%, PPV of 66.7%, NPV of 89.4%, with a total accuracy of 86%), and grading of steatosis by ultrasound. Conclusions RTE is beneficial in diagnosing and assessing NAFLD, especially in advanced cases “F3 and beyond.”